EFEK EKSTRAK KLOROFORM DAUN TAPAK DARA (Catharanthus roseus [L.] G. Don) var.albus dan roseus DALAM INDUKSI APOPTOSIS BERDASARKAN EKSPRESI PROCASPASE-3 PADA SEL HeLa - , RATIH KUSUMASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Perwinkle (Catharanthus roseus [L]. G.Don) is an herbal plant which widely spread in Indonesia. It has 2 varieties that is albus (white flower) and roseus (purple flower). Recent studies showed that perwinkle contains more than 100 types of indole alkaloids, thus has high potentiality as anticancer in testicular teratoma, Hodgkinâs lymphoma, leuchemic T-cell and ovarian cancer. Vincristine is one of perwinkleâs alkaloids thas has ability to induce apoptosis by activation of p53 gene. Objective of this study is examine the cytotoxicity effects and ability of white and purple perwinkle leaves to induce apoptosis in HeLa cells, based on expression of procaspase-3, the inactive form of caspase-3 (executioner caspase). Perwinkle leaves was extracted in chloroform, then cytotoxicity assay of extract was determined by IC50 values using the MTT assay method. After we got IC50 value, we analyzed the expression of procaspase-3 by Western blotting method and used concentration of extract equal with IC50 and 2 times IC50 value as treatment. Result showed that IC50 values of purple and white perwinkle leaves extract was 188.949 Î¼g/mL and 201.37 Î¼g/mL respectively. Hence, periwinkle leaves extract have moderate level of cytotoxicity for HeLa cell. Furthermore, the expression of procaspase-3 decreased after 48 hour treated with perwinkle leaves extract. It possibly that procaspase-3 already activated into caspase-3 which was executor of apoptosis. It can be concluded that both varieties of perwinkle (albus and roseus) have ability to induce apoptosis.